Beyond Technology: Exploring Religious Beliefs and Systems Thinking as Foundations for Renewable Energy Education - Nasrudin, Dindin; Rochman, Chaerul; Nugraha, Abdurrohman Khotim; Rahayu, Yayu Nurhayati; Muhammadi, Sani Insan (PAEDAGOGIA, 2026)
The global shift towards renewable energy demands an educational approach that transcends mere technical knowledge. This study posits that religious beliefs and systems thinking skills are crucial, yet often overlooked, foundations for effective renewable energy education. A cross-sectional survey was conducted among 200 Indonesian university students from diverse academic disciplines to explore this paradigm. Data were collected using a 9-item questionnaire focusing on two domains: religious beliefs (4 items) and systems thinking (5 items). The instrument’s content was validated by experts in physics education and environmental science, yielding high internal consistency with Cronbach’s alpha values of 0.92 for religious beliefs and 0.86 for systems thinking. Descriptive statistics were used to analyze the data. The results reveal that students possess a strong perceived moral alignment between religious values and environmental stewardship (M = 3.52) and a high readiness for systems thinking (M = 3.37). However, this study is limited by its reliance on self-reported data, which measures perceived readiness rather than actual performance. These findings suggest that integrating ethical drivers and analytical frameworks can foster a more holistic "Beyond Technology" pedagogical model. This study advocates for a culturally grounded approach to Education for Sustainable Development (ESD) by leveraging spiritual and cognitive assets to support the energy transition.